Asymmetric Effects of the Sustainable Energy Policy Index and Socioeconomic Development on the Ecological Footprint with Emphasis on Institutional Quality in Iran - Boloori, Jalaloddin; Damankeshideh, Marjan; Amin Rashti, Narsis; Mehrabian, Azadeh (Management Strategies and Engineering Sciences, 2026)
At present, economic development on the one hand and the preservation of the Earth’s environment on the other have become major challenges for humanity. Global warming, air pollution, marine pollution, soil erosion, desertification, and other environmental crises are the outcomes of human economic activities along the development path. If environmental quality, as the foundation of development, is neglected, not only will the development trajectory for future generations be halted, but it may also reverse, implicitly signaling future unsustainability. Since any effort to enhance human quality of life is realized within the environment, the condition of environmental resources significantly influences the sustainability or unsustainability of the development process. Accordingly, any discussion of sustainable development without considering environmental sustainability is incomplete. The ecological footprint reflects the extent of human use of natural resources and serves as an indicator of environmental sustainability. In this study, the role of institutional quality as a moderating factor in the relationship between energy policies, economic development, and environmental conditions is examined. The objective is to achieve a precise understanding of how economic and institutional variables influence environmental sustainability in Iran. This study investigates the asymmetric effects of the sustainable energy policy index and socioeconomic development on the ecological footprint, emphasizing the role of institutional quality in Iran over the period 1991–2024. To this end, the NARDL model is employed to assess the differential impacts of positive and negative changes in variables on environmental sustainability in both the short and long run. The estimation results indicate that, in the long run, improvements in institutional quality significantly reduce the ecological footprint; effective governance, corruption control, and enhanced institutional accountability play a moderating role in the relationship between economic development and environmental degradation. Furthermore, sustainable energy policies, through improving energy efficiency and expanding renewable energy sources, exert a significant negative effect on the ecological footprint, whereas reductions in these policies have a stronger asymmetric effect in increasing it. On the other hand, economic development and urbanization, if pursued without environmental considerations, lead to an increase in the ecological footprint; however, in the presence of high-quality institutions and sustainable energy policies, their adverse effects can be mitigated. Short-run results also indicate that positive shocks to institutional quality and renewable energy reduce the ecological footprint, whereas negative shocks in economic development and natural resource consumption exert destructive effects on the environment. Overall, the findings suggest that achieving sustainable development in Iran requires strengthening institutional quality, implementing sustainable energy policies, and directing economic development toward green growth.